2005
DOI: 10.1086/426400
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intermittent Preventive Treatment with Chemoprophylaxis for the Prevention of Malaria during Pregnancy in Mali

Abstract: In Mali, IPT with SP appears more efficacious than weekly chloroquine chemoprophylaxis in preventing malaria during pregnancy. These data support World Health Organization recommendations to administer at least 2 doses of IPT during pregnancy. In intensely seasonal transmission settings in Mali, >2 doses may be required to prevent placental reinfection prior to delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
104
3
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(133 citation statements)
references
References 27 publications
16
104
3
10
Order By: Relevance
“…Our findings confirm the beneficial effects of IPTp in pregnant women in terms of reduction of the prevalence of malaria as well as maternal anemia, which have been shown in other studies. [23][24][25][26] At delivery, however, there was a slight increase in malaria prevalence, although not reaching the level observed in first ANVs. The shorter duration of time intervals between ANV1 and ANV2, compared with ANV2 and delivery, suggests reinfection of the women after the levels of antimalarials have dropped below subtherapeutic concentrations.…”
Section: Discussionmentioning
confidence: 84%
“…Our findings confirm the beneficial effects of IPTp in pregnant women in terms of reduction of the prevalence of malaria as well as maternal anemia, which have been shown in other studies. [23][24][25][26] At delivery, however, there was a slight increase in malaria prevalence, although not reaching the level observed in first ANVs. The shorter duration of time intervals between ANV1 and ANV2, compared with ANV2 and delivery, suggests reinfection of the women after the levels of antimalarials have dropped below subtherapeutic concentrations.…”
Section: Discussionmentioning
confidence: 84%
“…This study sought to provide evidence of the efficacy of the later regimen in the treatment of uncomplicated malaria as the partner drug is used in intermittent preventive treatment in pregnant women (IPTp) and seasonal malaria chemoprevention (SMC) in children in Africa. [23][24][25][26] We evaluated efficacy of the combinations AL and AS+SP in children aged 6 months and older and adults living in a malaria-endemic area in Mali. We showed that AS+SP is as efficacious as the first-line treatment ACT with a high cure rate.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31][32] SP is recommended in IPTp and has been used in other interventions such as SMC in Africa. [23][24][25][26] There is a concern about the rapid emergence of SP resistance. One limitation of this study is the lack of genotyping data on molecular markers of SP resistance before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately two-fifths and three-fifths of healthcare providers still prescribe chloroquine and pyrimethamine respectively despite overwhelming evidence against such practice due to increasing resistance to these drugs, and reducing efficacy of chloroquine (CQ) chemoprophylaxis 15 and weekly pyrimethamine 16,17 . The possible reasons for this would include easy availability, affordability.…”
Section: Discussionmentioning
confidence: 99%